Childhood: Great challenges - Llanos Zuloaga, Martha (2023)
This article emphasizes the importance of the nexus interaction between early childhood or infancy period and the childhood itself. Establish the relationship between experiences within the initial education and primary education. The author is a worldwide advocator of children rights and a pioneer of children integrated development in Perú, in that capacity she gives a historical perspective of the importance and contributions of early childhood in Perú and its role within Latin America and the current national recognition of the status of General Directorate that was taken away 16 years ago. Since the last time issue of this journal was devoted to Early Childhood years this article poses priority to a crucial landmark within the organization of the Ministry of Education that represents a step forward within the fulfilment of children´s rights in Perú.